Pengaruh Kolektor Pelat Gelombang Dengan Dua Kaca Penutup Terhadap Penambahan Panas Untuk Meningkatkan Kinerja Solar Water Heater - Dian kusuma; Mustafa Mustafa; Sudarno Sudarno (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2019)
The worked principle of solar collector wave absorber plate was to transfer solar radiation to the worked fluid. The solar radiation that falls on the first glass was partially reflected, then on the second glass partially absorbed by the absorbent plate. The heat absorbed by the absorbent plate will be used to heat the worked fluid (water) between the absorbent plate and the storage plate. The purpose of this research was to design and make solar collector used wave plate with two cover glass. The addition of incomed water heat used temperatures of 30 ° C, 40 ° C, 50 ° C. The method used was used an expriment by analyzed the effect of initial heat addition on efficiency. From the results of test data obtained collector performance of solar water heater the greater the addition of heat used then the smaller the efficiency. Each of the average heat additions efficiency at 30 ° C was 19.66%, the temperature of 40 ° C was 17.75%, and the temperature of 50 ° C was 12.23%.